A new in situ strategy to eliminate partial internal short circuit in Ce0.8Sm0.2O1.9-based solid oxide fuel cells. Issue 25 (6th June 2017) - Gong, Zheng; Sun, Wenping; Cao, Jiafeng; Wu, Yusen; Miao, Lina; Liu, Wei
Abstract : A SrCeO3 -based electron-blocking layer was formed via an in situ reaction when a Sr-containing Ni-SrCe0.95 Yb0.05 O3− δ anode was employed for a Ce0.8 Sm0.2 O1.9 -based SOFC. Abstract : Partial internal short circuit resulting from the Ce 4+ /Ce 3+ redox reaction is currently one of the most critical issues that hinder the practical application of solid oxide fuel cells (SOFCs) with doped ceria electrolytes. In this work, a new strategy utilizing a Sr diffusion induced in situ solid-state reaction to generate a blocking layer to prevent Ce0.8 Sm0.2 O1.9 (SDC) from reduction is proposed for the first time. As a proof of concept, Ni-SrCe0.95 Yb0.05 O3− δ is deployed as a Sr source for the electron-blocking interlayer and was evaluated as an anode for SDC-based SOFCs. A thin interlayer composed of SrCe1− x (Sm, Yb) x O3− δ and SDC is formed in situ during the sintering process of the half cell due to the interdiffusion of metal cations, and the interlayer thickness is highly dependent on the sintering temperature. The high-resolution TEM results indicate that the SrCe1− x (Sm, Yb) x O3− δ perovskite phase is generated and coated on the SDC grains, forming an SDC@SrCe1− x (Sm, Yb) x O3− δ core–shell structure. The SrCe1− x (Sm, Yb) x O3− δ phase effectively suppresses the Ce 4+ /Ce 3+ redox reaction and hence eliminates electronic conduction through the electrolyte membrane. Consequently, the OCVs of the fuel cell are significantly improved after incorporating the electron-blocking interlayer and increase with increasing the interlayer thickness. The OCVs of the cell sintered at 1250 °C reach 0.962, 0.989, 1.017, and 1.039 V at 650, 600, 550, and 500 °C, respectively. The present results demonstrate that Ni-SrCeO3 -based composites are promising alternative anodes for CeO2 -based SOFCs towards enhanced working efficiency at high operating voltages.